2016
DOI: 10.1039/c5ra21085b
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of Cu(OH)2/CuO nanowires as a novel sensitivity enhancer of the luminol–H2O2chemiluminescence system: determination of cysteine in human plasma

Abstract: Cu(OH)2/CuO nanowires as a sensitivity enhancer in luminol–H2O2 chemiluminescence system and its application for the determination of cysteine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The E g value of the CuO NPs was found to be 3.3 eV in this study. The feature of the plot indicated that it had a direct transition due to the linear absorption at the end of the plot [50]. The higher band gap energy of the CuO NPs than the reported value (1.9-2.1 eV) could be related to the quantum confinement effect that is the band gap increase with a reduction in particle size [51].…”
Section: Structural Analysis Of Cuomentioning
confidence: 78%
“…The E g value of the CuO NPs was found to be 3.3 eV in this study. The feature of the plot indicated that it had a direct transition due to the linear absorption at the end of the plot [50]. The higher band gap energy of the CuO NPs than the reported value (1.9-2.1 eV) could be related to the quantum confinement effect that is the band gap increase with a reduction in particle size [51].…”
Section: Structural Analysis Of Cuomentioning
confidence: 78%
“…(iii) When H 2 O 2 is added to the system, G4/MOFzyme would react with H 2 O 2 to produce a highly reactive hydroxyl radical OH · followed by the reaction with luminol anion and HO 2 – to facilitate the formation of luminol radicals and O 2 · – . Finally, luminol radicals react with O 2 · – to generate strong CL emission, which is beneficial for the accurate detection of target miRNAs and long-lasting CL imaging. , …”
Section: Resultsmentioning
confidence: 99%
“…(iii) When H 2 O 2 is added to the system, G4/MOFzyme would react with − to generate strong CL emission, which is beneficial for the accurate detection of target miRNAs and long-lasting CL imaging. 74,75 Applications to CL Printing. Due to the excellent catalytic ability of the G4/MOFzyme, we sought to apply it to other fields.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The features of peaks at 587, 1000 and 3576 cm −1 are related to the C-O stretching vibration and C-O-H bending vibration, as well as O-H stretching vibration proving the successful synthesis of coated Cu(OH) 2 with Fe 3 O 4 @SiO 2 . In addition, 1500 cm −1 belongs to H-O-H bending vibrations of H 2 O adsorbed onto the FSCNWs lattice (figure 5) [35,46,47].
Figure 5FT-IR spectra of Fe 3 O 4 @SiO 2 /Cu(OH) 2 .
…”
Section: Resultsmentioning
confidence: 99%